Deep genetic divergences and geographic distribution of the red algal genus Caulacanthus (Gigartinales) - Yang, Mi Yeon; Kim, Myung Sook (Frontiers in Marine Science, 2023)
An increasing number of studies have demonstrated that genetic differentiation and cryptic diversity in the sea occur over considerably smaller spatial scales than previously comprehended, considering the wide distribution range of many morphologically defined macroalgal species. However, knowledge of the turf-forming red alga Caulacanthus is incomplete regarding its species diversity, as well as genetic differentiation within the genus. We analyzed Caulacanthus specimens from the NW Pacific, NE Pacific, Central Pacific, SW Pacific, SE Indian, NE Atlantic, and SE Atlantic Ocean using mitochondrial cytochrome oxidase subunit I (COI-5P), plastid ribulose-1,5-bisphosphate carboxylase/oxygenase (rbcL), and Rubisco spacer (rbcL-S). The objectives of this study were to 1) determine the number of species that exhibit the morphology of C. ustulatus, 2) investigate the present distribution pattern of Caulacanthus species, and 3) estimate the degree of genetic connectivity between the populations of Caulacanthus species from different regions. Our results revealed molecular evidence that the genus Caulacanthus comprises of at least seven species with deep genetic divergence, which is indicative of not only a strong geographical subdivision but also a relatively long temporal discontinuity. Most species exhibited limited geographic distribution, showing considerable genetic divergence in the populations isolated by distance. Our study provides evidence of a greater evolutionary independence of Caulacanthus populations, which have undergone a series of allopatric diversification events.